The stone king - McDonald, Kel (Dark Horse Books, 2022)
"Ave has decided to illegally harvest healing moss from the Stone King, a mighty giant who roams the lands. Her theft goes even better than she could have dreamed. But what she thought would buy her a ticket to adventure and a better life, brings disaster instead. Now her home is in danger and fixing her mistakes is the city's only hope"--